An adaptive power controlled routing protocol for underwater sensor network. (2015) - Al-Bzoor, Manal; Zhu, Yibo; Liu, Jun; Ammar, Reda; Cui, Jun-Hong; Rajasekaran, Sanguthevar
Geo-routing protocols can provide the scalability, robustness, lower overhead and energy efficiency requirements for underwater sensor networks (UWSNs). However, these protocols require localisation service, which is another challenging problem. In this paper, we introduce a novel energy efficient schema that does not need location information. In this schema, nodes assign themselves to concentric layers around sink nodes and routing paths are determined on the fly based on nodes' layers and residual energy information. Nodes can adaptively adjust their transmission power level to cater for network mobility and residual energy constraints. Extensive simulation results show that our routing protocol achieves high delivery ratio and low energy consumption while reducing end to end delay when compared with other routing strategies. In particular, our schema can guarantee a relatively higher delivery ratio in presence of mobility.